2015
DOI: 10.1016/j.jocrd.2015.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic process during exposure: Habituation model

Abstract: The current paper outlines the habituation model of exposure process, which is a behavioral model emphasizing use of individually tailored functional analysis during exposures. This is a model of therapeutic process rather than one meant to explain the mechanism of change underlying exposure-based treatments. Habitation, or a natural decrease in anxiety level in the absence of anxiety-reducing behavior, might be best understood as an intermediate treatment outcome that informs therapeutic process, rather than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(62 citation statements)
references
References 51 publications
1
58
0
3
Order By: Relevance
“…For example, researchers found that individuals with agoraphobia ventured further from their homes during exposure exercises when told that such exercises were part of treatment as opposed to merely assessment (Southworth & Kirsch, 1988). While there a handful of conceptualizations of the process of change for ERP, two somewhat distinct theory-driven approaches to framing ERP for OCD currently exist, including (a) traditional cognitive-behavioral approaches that emphasize anxiety reduction and the modification of dysfunctional cognitions (Benito & Walther, 2015;Foa, Huppert, & Cahill, 2006), and (b) acceptance and commitment therapy-based (ACT) approaches that emphasize willingness to experience anxiety, valued living, and cognitive defusion (fostering an "observer perspective" with regard to private experiences; Twohig, 2009;. These frameworks also incorporate distinct, yet overlapping, goals of exposure (anxiety reduction vs. valued living), approaches to targeting the anxiety provoked during exposure exercises (habituation vs. acceptance), and approaches to addressing fear-based cognitions (testing and modifying vs. defusing from them; Arch et al, 2015).…”
Section: Obsessive-compulsive Disorder: a Randomized Controlled Trialmentioning
confidence: 99%
“…For example, researchers found that individuals with agoraphobia ventured further from their homes during exposure exercises when told that such exercises were part of treatment as opposed to merely assessment (Southworth & Kirsch, 1988). While there a handful of conceptualizations of the process of change for ERP, two somewhat distinct theory-driven approaches to framing ERP for OCD currently exist, including (a) traditional cognitive-behavioral approaches that emphasize anxiety reduction and the modification of dysfunctional cognitions (Benito & Walther, 2015;Foa, Huppert, & Cahill, 2006), and (b) acceptance and commitment therapy-based (ACT) approaches that emphasize willingness to experience anxiety, valued living, and cognitive defusion (fostering an "observer perspective" with regard to private experiences; Twohig, 2009;. These frameworks also incorporate distinct, yet overlapping, goals of exposure (anxiety reduction vs. valued living), approaches to targeting the anxiety provoked during exposure exercises (habituation vs. acceptance), and approaches to addressing fear-based cognitions (testing and modifying vs. defusing from them; Arch et al, 2015).…”
Section: Obsessive-compulsive Disorder: a Randomized Controlled Trialmentioning
confidence: 99%
“…Secondly, the club's capacity to provide opportunities for the child to try out football before enrolling in the activity was discussed to be helpful in encouraging the child to decide if they would enjoy the activity. Indeed, theories of graded exposure suggest that gradual exposure to a potentially stressful event can reduce anxiety leading to the event [42].…”
Section: Discussionmentioning
confidence: 99%
“…There are several different theoretical frameworks a therapist could use to approach exposure (see Conelea & Freeman, ). One of these frameworks is the habituation model, which proposes that exposure reduces anxiety through habituation to feared stimuli, and that the process of habituation is passive and internal (Benito & Walther, ). According to this theory, optimal exposure would involve activating the fear, minimizing behaviors that function to reduce anxiety (i.e., negative reinforcement via rituals, avoidance), and allowing time to pass so that anxiety will run its course and attenuate on its own (i.e., habituation).…”
Section: Functional Variations Of Same Topographical Presentation Of mentioning
confidence: 99%